Measles Vaccine and Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The relationship between acute encephalopathy followed by permanent brain injury or death associated with further attenuated measles vaccine was evaluated in 48 children, ages 10 to 49 months, reported to the National Vaccine Injury Compensation Program, Rockville, MD.